Bile acids lower triglyceride levels via a pathway involving FXR, SHP, and SREBP-1c - Watanabe, Mitsuhiro (American Society for Clinical Investigation, 2004)
We explored the effects of bile acids on triglyceride (TG) homeostasis using a combination of molecular, cellular, and animal models. Cholic acid (CA) prevents hepatic TG accumulation, VLDL secretion, and elevated serum TG in mouse models of hypertriglyceridemia. At the molecular level, CA decreases hepatic expression of SREBP-1c and its lipogenic target genes. Through the use of mouse mutants for the short heterodimer partner (SHP) and liver X receptor (LXR) α and β, we demonstrate the critical dependence of the reduction of SREBP-1c expression by either natural or synthetic farnesoid X receptor (FXR) agonists on both SHP and LXRα and LXRβ. These results suggest that strategies aimed at increasing FXR activity and the repressive effects of SHP should be explored to correct hypertriglyceridemia.